2012
DOI: 10.4414/smw.2012.13658
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral body stenting / stentoplasty

Abstract: Osteoporotic vertebral fractures are frequent. Although the majority of fractures follow a benign course, there are certain fracture types which result in severe spinal deformity and / or are associated with neurological complications. These patients should be detected early and undergo surgical treatment. Vertebroplasty remains an important and effective treatment option for acute painful vertebral fractures showing progressive collapse. By this procedure the fracture can be stabilised, the pain is controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 16 publications
3
9
1
1
Order By: Relevance
“…32,33 Many authors have found good to excellent results in terms of pain improvement, quality of life and kyphosis restoration. 32,34,35 Few studies have compared stentoplasty with other modalities.…”
Section: The Best Methods Of Cement Augmentation For Ovfsmentioning
confidence: 99%
“…32,33 Many authors have found good to excellent results in terms of pain improvement, quality of life and kyphosis restoration. 32,34,35 Few studies have compared stentoplasty with other modalities.…”
Section: The Best Methods Of Cement Augmentation For Ovfsmentioning
confidence: 99%
“…In cement augmentation techniques, in addition to vertebroplasty and kyphoplasty, Stentoplasty has been recently described where a cavity is created within the vertebral body by using a titanium device and kept in place for cement injection. 46 It was found to have good to excellent results in pain improvement, quality of life and kyphosis restoration.…”
Section: Other Novel Strategiesmentioning
confidence: 96%
“…Reducing the volume of cement as the primary stabilizer in vertebral compression fractures can also reduce the likelihood of cement leakage (11,12). Unfortunately, the recovery of vertebral body height may be only temporary as there is often a total or partial vertebral body collapse after the balloon is deflated (13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%